Zastosowanie oznaczen wybranych hormonów we krwi w ocenie adaptacji do wysilku u sportowców dyscyplin wytrzymaLosciowych - Obminski, Z. (Medycyna sportowa, 2000)
The paper discusses the biological significance of steroid hormones - cortisol and testosterone - controlling the metabolism in prolonged work in various endurance athletes, including competitive cyclists. Determinations of those hormones may be applied to the assessment of athlete's fitness and of the biological cost of an exhausting exercise. Moreover, adaptation to exercise under moderately hypoxic conditions and elevated ambient temperature was discussed.